RASIO KEUANGAN DAN PENGARUHNYA TERHADAP PERGERAKAN HARGA SAHAM SEKTOR PROPERTI YANG LISTING DI BURSA EFEK INDONESIA - Tri Kunawangsih Purnamaningrum (Media Ekonomi, 2018)
The research is analyzing the effect current ratio, Return on Equity, dividend per share, towards the property stock price in Indonesia Stock Market. The research methodology used is quantitave deskriptif. The data used in this research was quarterly data during period 2011-2016. The estimation method is based on pooled OLS regression with fixed effects and random effects models.   Historical data was taken Indonesian Stock Market, Statictic Center Beaurau, Bank of Indonesia report and Indonesia Capital Market Directory. The results of the study showed current ratio and dividen per share has positiv significant influence toward property stock price. While Return on Equity has negative significant toward property stock price.